Internal Control System as a Mediator of the Relationship between Good Corporate Governance and Fraud Prevention in Rural Banks in Bali - Putu Yudha Asteria Putri; Ni Putu Monika Cahyanti; Ni Nyoman Sri Rahayu Damayanti; I Wayan Kartana; I Gusti Ngurah Agung Kepakisan Mandala (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
Rising fraud incidents at Bali’s Rural Banks (BPR) threaten public confidence and the stability of financial institutions. Conflicting results in earlier studies about whether Good Corporate Governance directly prevents fraud reveal a research gap that calls for further exploration, especially regarding potential mediating factors. This study investigates how Good Corporate Governance influences fraud prevention and assesses whether the internal control system functions as a mediator. Using a quantitative survey design, the research sampled 177 managers and employees from BPRs in Bali through saturated sampling. Data were analyzed with Structural Equation Modeling using Partial Least Squares (SEM-PLS). Findings show that Good Corporate Governance positively and significantly affects both fraud prevention and the internal control system. The internal control system likewise has a positive and significant impact on fraud prevention and partially mediates the relationship between Good Corporate Governance and fraud prevention. The results suggest that effective fraud reduction in the banking sector requires translating good corporate governance into strengthened internal control systems